2-[2-Hydroxyimino-2-(3-methyl-3-phenylcyclobutyl)ethyl]isoindole-1,3-dione - Özdemir, N; Dinçer, M; Yilmaz, I; Çukurovali, A (Int Union Crystallography, 2004)
The molecules of the title compound, C21H20N2O3, are linked by O-H...O and C-H...N hydrogen bonds, and by pi-pi interactions. The cyclobutane ring is puckered, with a dihedral angle of 11.55 (3)degrees between the two planes. The phenyl ring shows positional disorder.
Keywords: Oxiconazole; Thalidomide; Crystal